The relationship between oral health status, loneliness, and sleep quality among the migrant elderly following children in Weifang, Shandong Province, China: A comparative analysis on different migration types - Jiang, Xiaoxu; Liu, Guangwen; Xu, Jing; Li, Hexian; Wang, Jieru; Pang, Mingli; Li, Shixue; Xu, Lingzhong; Guo, Xiaolei; Kong, Fanlei (Frontiers in Public Health, 2023)
This study aimed to explore the association between oral health status, loneliness and sleep quality among the migrant elderly following children (MEFC) in China, and furtherly clarify the migration type disparity on the above relationship. A cross-sectional survey was conducted in Weifang, Shandong Province in 2021 by using a multi-stage cluster random sampling to collect data from MEFC aged 60 years and above. A total of 613 respondents (525 rural-to-urban and 88 urban-to-urban) were included in the final database. Chi-square test, t-test, and structural equation modelling (SEM) were used to explore the relationship between oral health status, loneliness, and sleep quality among the rural-to-urban (RTU) and urban-to-urban (UTU) MEFC. The mean ± S.D. of oral health status, loneliness and sleep quality were 54.95±6.47, 8.58±3.03, 4.47±3.60 respectively. SEM showed that oral health status was significantly and positively associated with sleep quality both for the RTU and UTU MEFC, while the correlation was slightly stronger in UTU MEFC. There was a significant negative correlation between oral health status and loneliness in both groups, and the correlation was stronger in the UTU MEFC. Significantly negative correlation between loneliness and sleep quality was observed for RTU MEFC, but no correlation for UTU MEFC.